(untitled) (Research, Society and Development, 2021)
Objective: to map how adverse events are notified in the mobile pre-hospital emergency service. Method: This is a scope review protocol, carried out according to the methodological recommendations of the Joanna Briggs Institute (JBI) and the PRISMA Extension for Scoping Reviews (PRISMA-ScR) checklist, in order to answer the research question “How are the notifications of adverse events in mobile pre-hospital emergency services?”, prepared according to the acronym PCC (Population; Concept; Context), where P refers to pre-hospital emergency service professionals, C to notification of adverse events and C to the Service pre-hospital emergency service. After selecting the descriptors, a previous search in Medline (PubMed) and Embase was performed, followed by the analysis of the words in the text contained in the title and abstract in order to identify new terms. Then, a new complete search will be performed in other selected databases and in gray literature, for the final selection of studies.